Dynamic switching of cell–substrate contact sites allows gliding diatoms to modulate the curvature of their paths - Stefan Golfier; Veikko F. Geyer; Leon Lettermann; Ulrich S. Schwarz; Nicole Poulsen; Stefan Diez (Proceedings of the National Academy of Sciences, 2026)
The directed motility of unicellular organisms is critical for their survival and ecological success, yet the mechanisms that enable rigid-walled diatoms to dynamically reorient and alter the shape of their trajectories remain poorly understood. Here, we investigate the gliding motility of Craspedostauros australis , a raphid pennate diatom that moves rapidly across submerged surfaces using an intracellular actomyosin motility complex and the secretion of adhesive extracellular polymeric substances (EPS) strands through slit-like openings termed raphes. Using high-precision single-cell tracking, scanning electron microscopy (SEM), interference reflection microscopy (IRM), and mathematical modeling, we reveal how diatoms achieve diverse path curvatures by dynamically modulating the location of raphe–substrate contact and switching between one- and two-raphe branch contact gliding. Our results indicate that local curvature variations along the raphes dictate trajectory shapes, with one-raphe branch contact gliding producing highly curved paths, while two-raphe branch contact gliding results in paths of lower curvature. IRM imaging further confirms that transitions between these gliding modes underlie abrupt changes in path curvature and cell reorientation. This dynamic raphe-switching mechanism is conserved across cell sizes and correctly predicts the increased path curvatures observed in smaller cells according to their more pronounced local raphe curvature. By quantitatively linking raphe geometry, cell–substrate attachment dynamics and motility patterns, our study provides insights into the motility mechanism that allows diatoms to adapt their movement to complex environments.